Determination of dosimetric properties of MgO doped natural amethyst samples. (October 2016) - Nur, N.; Guckan, V.; Kizilkaya, N.; Depci, T.; Ahmedova, C.; Yucel, A.; Ozdemir, A.; Altunal, V.; Koc, V.; Yegingil, Z.
Abstract: In this paper, the thermoluminescence (TL) dosimetric characteristics of MgO doped natural amethyst samples (Mg-NA) are presented. The morphologies and chemical structures of the powder form samples were identified using XRD, FTIR, SEM, SEM mapping and EDX. Comparison of the TL intensities showed that 10 wt% Mg-NA was nearly 150 times more sensitive than undoped amethyst and the main dosimetric properties proved that 10 wt% Mg-NA may be a promising phosphor for clinical and radiotherapy purposes. Highlights: Magnesium was doped into natural amethyst quartz sample (NA). The chemical structures of the undoped and MgO doped NA were identified and compare with each other. The main dosimetric properties of MgO doped NA were investigated. MgO doped NA as a phosphor might be used in many fields concerning with the dose range from 0.1 Gy up to 100 Gy.